Mesenchymal Stromal Cell-Derived Extracellular Vesicles Protect Against Acute Kidney Injury Through Anti-Oxidation by Enhancing Nrf2/ARE Activation in Rats - Guangyuan Zhang; Xiangyu Zou; Yeqing Huang; Feng Wang; Shuai Miao; Guohua Liu; Ming Chen; Yingjian Zhu (Karger Publishers, 2016)
Background/Aims: Anti-oxidation is an effective strategy for curing acute kidney injury (AKI). Herein, we suggest that extracellular vesicles (EVs) derived from mesenchymal stromal cells (MSCs) might play an anti-oxidative role by enhancing Nrf2/ARE activation in AKI. Methods: EVs isolated from the conditioned medium of human Wharton's Jelly mesenchymal stromal cells and human foreskin fibroblast were intravenously injected in rats immediately after 45 min of unilateral kidney ischemia. Animals were sacrificed 24 h after injury. Results: Results showed that renal tubular injury was alleviated and renal function was improved by MSC-EVs. Cell apoptosis and sNGAL levels, which reflect kidney cell injury, were reduced. Moreover, MSC-EVs decreased oxidative stress in injured kidney tissues and NRK-52E cells under hypoxia injury. Nrf2/antioxidant response element (ARE) enhancement and HO-1 up-regulation were further observed after MSC-EV treatment both in vivo and in vitro. Conclusions: MSC-EVs may protect against AKI possibly through anti-oxidation by enhancing Nrf2/ARE activation.